Analisis Indeks Fungsi Saluran Dan Bangunan Irigasi Sugihan Kiri Menggunakan Pendekatan Indeks Kondisi pada Daerah Irigasi Rawa - Ratih Baniva; Andre Wibowo (Jurnal Konstruksi, 2025)
The Sugihan Kiri Tidal Irrigation Area (DIR) is one of the key irrigation regions in Muara Sugihan District, playing a strategic role in supporting agricultural productivity. However, damage to irrigation canals and structures can hinder water distribution and reduce the efficiency of irrigation network management. This study aims to obtain the function index of the canals and irrigation structures in the Sugihan Kiri tidal area as a basis for maintenance recommendations. The research was conducted through field surveys (walkthroughs) involving irrigation asset inventory, measurement of canal and structure damage, and documentation of existing conditions. The data were analyzed using a condition index approach to determine the functional level of canals and structures, followed by identifying appropriate treatment measures. The results show that the canal function index of DIR Sugihan Kiri is 60.18%. Of the 15 primary canals, 6 require routine maintenance, 5 require periodic maintenance, and 4 require rehabilitation. For the 248 secondary canals, 72 require routine maintenance, 86 require periodic maintenance, and 90 require rehabilitation. The function index of irrigation structures in DIR Sugihan Kiri reaches 62.39%, with 93 structures recommended for periodic maintenance and 8 structures requiring rehabilitation.